Growth performance and carcass characteristics of finishing beef steers implanted with component TE-S or component TE-S with Tylan - Dicke, B.; Erickson, G.E.; Klopfenstein, T.J.; Botts, R.T.; Anderson, P.T.; Depenbusch, Brandon E.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Component TE-S and Component TE-S with Tylan growth-promoting implants were compared in an experiment conducted at a commercial feedlot operation (Ward Feed Yard; Larned, Kansas) to evaluate effects on growth performance and carcass characteristics. Crossbred steers (n=1843; 827 lb body weight) were implanted with either Component TE-S or Component TE-S with Tylan and were fed a finishing ration based on steam-flaked corn for an average of 116 days before slaughter. Cattle were assigned randomly to the implant treatments at processing and were allotted to 12 pens, containing an average of 154 steers each. No differences were detected in dry matter intake (P=0.18), average daily gain (P=0.41), or feed efficiency (P=0.59) of cattle administered the different implants. Component TE-S with Tylan produced fewer (P<0.05) buller steers. Cattle implanted with Component TE-S with Tylan were more heavily conditioned than cattle implanted with Component TE-S. Cattle with the implant including Tylan had a greater percentage of USDA Choice or Prime carcasses (P=0.11) and a greater percentage of USDA Yield Grade 4 carcasses (P=0.03). Component TE-S with Tylan also tended to produce fewer (P=0.12) USDA Yield Grade 1 carcasses compared with cattle implanted with Component TE-S. Total carcass value was also greater for the Component TE-S with Tylan cattle, as calculated by either a muscle-based or quality-based marketing grid. Inclusion of a pellet of the antibiotic Tylan within Component TE-S implants seems to result in modest changes in carcass fattening, as well as significant reductions in the incidence of buller activity among feedlot steers.
Keywords: Beef; Component TE-S; Component TE-S with Tylan